Effects of B2 nanoprecipitates on the phase stability and pseudoelastic behavior of Fe-Mn-Al-Ni shape memory alloys - la Roca, Paulo Matías (2015)
Samples of a Fe-Mn36-Al15-Ni7.5 shape memory alloy were subjected to different thermal treatments at 200°C (namely for 0 min, 10 min, 20 min and 3 h) in order to evaluate the evolution of the coherent precipitates related to the pseudoelastic behavior. After performing the thermal treatments, samples were studied by means of electrical resistivity in experiments aimed at evaluating the effect of precipitation on the martensitic transformation temperatures and at determining the possible effects of thermal cycling. Mechanical tests were performed to measure the degree of pseudoelastic recovery for each thermally treated sample. Evidences of pseudoelastic behavior were found even in samples subjected to a rather short treatment such as 20 min after three thermal cycles. Transmission electron microscopy (TEM) observations were performed in order to identify the distribution and size of B2 nanoprecipitates after the various thermal treatments.